Nanofibrous bio-inorganic hybrid structure formed through self-assembled peptide (FKFSFEFEFKFK): article - Haidir, Nurul Akma; Tan, Huey Ling; Mulana, Farid (2017)
The purpose of this study is to synthesis and characterized Hydroxyapatite (HAP), to investigate and study the hybrid structure that will form through self-assembled between HAP and (FKFSFEFEFKFK) peptide and to characterize the hybrid structure between HAP and (FKFSFEFEFKFK) peptide in different medium of distilled water and potassium chloride. The technique of synthesizing HAP was done by wet chemical method where Calcium Nitrate Tetra Hydrate was allowed to mix with Sodium Di-hydrogen Phosphate in deionized water producing calcium/phosphorus (Ca/P) with ratio 0f ∼1.67. The pH was adjusted until reaching pH7 where HAP is best work at pH7 condition. Then the HAP synthesis was used to mineralize with peptide (FKFSFEFEFKFK). The assembly nanoparticles form through the mineralization was allowed to characterize by using Fourier transform infrared spectroscopy (FTIR), Powder Xray diffraction (XRD), Inductive coupling plasma (ICP) and under microscope. Fourier transforms infrared spectroscopy (FTIR) was used to characterize the functional groups of synthesis HAP nanoparticles on molecular level. Powder X-ray diffraction (XRD) was used to see the selected reactions on the surface of HAP such as its intrinsic properties and crystalline structure while Inductive coupling plasma (ICP) monitor the concentration [Ca2+] of the solution phase during the mineralization. Observation under microscope was done to observe sample surface structure and the size distribution. In summary, it shows that the synthesis of HAP is maintained based on its molecular level, intrinsic properties and crystallinity. Mineralization under medium distilled water can form a better and clear size distribution compared to under medium potassium chloride.